2017
DOI: 10.3390/su9122336
|View full text |Cite
|
Sign up to set email alerts
|

Ambidextrous Leadership and Sustainability-Based Project Performance: The Role of Project Culture

Abstract: Most studies in the project management field emphasized the effects of leaders or managers, but these effects have rarely been examined at the project level. To cover this research gap, this study applies organizational ambidexterity theory to examine the effects among ambidextrous leadership, ambidextrous culture and sustainability-based project performance. Using a valid sample of 217 project leaders and members from Chinese construction projects, the method of multiple linear regression was adopted to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 89 publications
1
31
0
Order By: Relevance
“…innovative behavior) in temporary organization context. Even though the potential of organizational culture to be a moderator in the relationship between leadership and organizational outcomes has been identified (Han et al , 2016; Zheng et al , 2017), this study demonstrates the knowledge on the congruence perspective of leader-rated variable and cultural variable in understanding the motivation mechanism of followers’ innovative behavior in construction project setting. Moreover, this study not only considers the role of the followers’ perceptions in line with Li et al (2013), but also pays attention to the role of the followers’ outcomes (e.g.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…innovative behavior) in temporary organization context. Even though the potential of organizational culture to be a moderator in the relationship between leadership and organizational outcomes has been identified (Han et al , 2016; Zheng et al , 2017), this study demonstrates the knowledge on the congruence perspective of leader-rated variable and cultural variable in understanding the motivation mechanism of followers’ innovative behavior in construction project setting. Moreover, this study not only considers the role of the followers’ perceptions in line with Li et al (2013), but also pays attention to the role of the followers’ outcomes (e.g.…”
Section: Introductionmentioning
confidence: 67%
“…According to the previous research, the outcomes (e.g. performance) of construction projects are theoretically relevant to effective leadership styles (Odusami et al , 2003; Tyssen, Wald and Spieth, 2014) and organizational cultures (Zheng et al , 2017). Some current studies (e.g.…”
Section: Theories and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aronson [49] explored the influence of leader styles on project culture. Furthermore, Zheng et al [46] pointed out that ambidextrous leadership positively influenced ambidextrous culture. Kumaraswamy et al [70] shed light on professional and individualistic subcultures.…”
Section: Factors Influencing Project Culturementioning
confidence: 99%
“…In recent years, many scholars have conducted many empirical studies to explore the role of TL in project success [ 10 , 11 ]. On the one hand, most researchers have shown that TL can promote project success.…”
Section: Introductionmentioning
confidence: 99%